Stakeholders and web-based environmental disclosure - Muhammad Hamdan Sayadi; Doddy Setiawan; Y. Anni Aryani; Sri Hartoko (Proceeding International Conference on Accounting and Finance, 2025)
Based on stakeholder theory, this study investigates the impact of various types of stakeholder pressure on web-based environmental disclosure (WED) in Southeast Asia mining industry. Some previous studies have focused on investigating the influence of various company characteristics on WED. Previous literature has shown that there has been no research investigating the influence of employees, competitors, and creditors on WED. This study uses all mining companies registered in the capital markets of Southeast Asian countries. The results of the study show that employees and competitors have a positive and significant influence on WED. Meanwhile, creditors show insignificant influence.